Answer:
Answer explained below
Step-by-step explanation:
the equation of motion when an object is accelerated is given by:
[tex]x = x_{0}+v_{0}t+\frac{1}{2}at^{2}[/tex] where
x - is the current position(or displacement) of the body
x0 is the initial position
v0 is the initial velocity
a is acceleration
t is time
We rewrite the equation
[tex]s(t) = 35t - 16t^{2}[/tex] which is similar to the equation above, which means we can rewrite the following equation like this:
[tex]s(t) = 35t - \frac{32}{2} t^{2}[/tex]
so, in our case:
x0 = 0
v0 = 35 m/s
Now, since this is an accelerated motion it means that the velocity of the body changes as well due to acceleration with the equation:
[tex]v(t) = v_{0}+at[/tex]
acceleration is negative, therefore:
[tex]v(t) = 35 - 32t[/tex]
t = 1 results:
[tex]v(1) = 35 - 32 = 3 ft/s[/tex]